Answer:
(-4, -4) and (-6, -4)
Explanation:
Subtract the first equation from the second to eliminate y.
(y) -(y) = (2x^2 +20x +44) -(-3x^2 -30x -76)
0 = 5x^2 +50x +120
0 = x^2 +10x +24
0 = (x +4)(x +6)
Solutions are values of x that make the factors zero:
x = -4, x = -6
The corresponding y-values are found by putting these values of x into either polynomial equation.
y = 2((x +10)x +22) . . . . . rearrange the second equation to Horner form
y = 2((-4 +10)(-4) +22) = 2(6(-4) +22) = -4 . . . . for x = -4
y = 2((-6 +10)(-6) +22) = 2(4(-6) +22) = -4 . . . . for x = -6
The solutions are (-4, -4) and (-6, -4).